Financial strain in the United Kingdom. (4th July 2017) - French, Declan
Abstract: UK households have been exposed to economic recession followed by a government programme of austerity, putting many under severe financial strain. Using UK longitudinal household data, we find that the feeling of not being able to cope financially matters for individual mental health and general health status even when controlling for individual heterogeneity and potential reverse causation. We develop a theoretical model which brings some of the rigour of lifetime economic decision-making models to bear on our understanding of the causes of financial strain. Our estimation results for this model highlight that shocks to how we view our financial situation are more important for subjective financial well-being than not having enough income or being liquidity constrained. Recent welfare and pension reforms intended to reduce budget deficits may have exacerbated financial strain and thus increased public healthcare costs. In the case of disability benefits reform, we find that the uncertainty generated by an opaque process of reassessment caused financial strain to increase even when households were not materially worse off.